Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/iej.13096
|View full text |Cite
|
Sign up to set email alerts
|

Maternal apical periodontitis is associated with insulin resistance in adult offspring

Abstract: Aim To investigate the plasma concentrations of glucose, insulin and tumour necrosis factor‐α (TNF‐α) of rats with maternal apical periodontitis (AP) and to explore the effect of maternal inflammation on the initial steps of insulin signalling and the inflammatory pathway in the gastrocnemius muscle (GM) and periepididymal white adipose tissue (pWAT) of adult offspring. Methodology Fifteen female Wistar rats were distributed into a control group (CN), a group with 1 tooth with AP (1AP) and a group with 4 teeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 39 publications
(59 reference statements)
3
29
1
Order By: Relevance
“…Another study reported that in adult rats, the offspring of rats with AP had insulin resistance, increased plasma concentration of TNF‐α, changes in the inflammatory pathway (increased IKKα/β phosphorylation status) and insulin signalling (decreased pp185 tyrosine phosphorylation status and increased IRS‐1 serine phosphorylation status) in muscle tissue and WAT (Tsosura et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that in adult rats, the offspring of rats with AP had insulin resistance, increased plasma concentration of TNF‐α, changes in the inflammatory pathway (increased IKKα/β phosphorylation status) and insulin signalling (decreased pp185 tyrosine phosphorylation status and increased IRS‐1 serine phosphorylation status) in muscle tissue and WAT (Tsosura et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there were no differences in this parameter in muscle tissue of adult rats, offspring of rats with AP (Tsosura et al . 2019) or PD (Mattera et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, there was an increase in the TNF‐α plasma concentration in the 1AP‐o and 4AP‐o groups compared with the CN‐o group (Tsosura et al, 2019). However, in the present study, there was no difference in TNF‐α gene expression and its protein content in the GM amongst the groups, indicating that the GM is not a source of this inflammatory cytokine, and other tissues, such as the adipose tissue, may contribute to the increase in the TNF‐α plasma concentration.…”
Section: Discussionmentioning
confidence: 85%
“…Tsosura et al (2019) reported that maternal apical periodontitis (AP) was associated with IR, increased TNF‐α plasma concentration, impairment in the initial step of insulin signalling and activation of the inflammatory pathway (IKKα/β) in the gastrocnemius muscle (GM) of adult offspring of rats. However, the mechanisms involved in this IR are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation